Effect of cinnamon extract on physicochemical properties of low fat yoghurt - Marpana, R. A. U. J. (My University, 2016)
It is recommended that everyone to consume food from animal origin as a part of their diet. Such as milk and milk allied products, meat and egg. But milk and allied products are preferred and consumed by all including vegetarians. Yoghurt is one of the milk allied product which is a popular desert and it is good source of animal protein minerals and vitamins. A study was carried out to produce a fermented milk product called Yoghurt with the value addition of cinnamon water extract and oil extract. There have been four types of yoghurt were prepared .No. I - Low fat cinnamon yoghurt (with Skim milk, full cream milk powder and Sugar),No.2 - Low fat cinnamon yoghurt (With Skim milk, sugar and without full cream milk powder),No.3 - Low fat cinnamon yoghurt (With Skim milk, With Full cream milk powder and without sugar), No.4 —Low fat cinnamon yoghurt (with Skim milk and without full cream milk powder and sugar).Sensory analysis was carried out for three different mix of yoghurt and cinnamon extract for each product. The best ratio of selected yoghurt mix and water extract for each type is 65:15, 65:15, 70:10 and 70:10 respectively. Proximate composition (fat, protein, moisture, total solids and ash) and Physical parameters (pH and Acidity) of the final product was investigated using AOAC procedures. Minerals such as Calcium and phosphorous were analyzed by the method described in By Vogel's Method, 1989 and Asian manuals 2011 respectively .pH and Acidity of all types of yoghurts were determine during the storage period. The proximate analysis revealed that all the products contain fat between 0.3-0.5%, Protein 3-3.5%, Moisture 76-79% , Ash 0.7-0.72% , Total solid 20-23%, Calcium 13-18mg/bOg and Phosphorous I 69-324mg/i 00g. pH of the cinnamon yoghurts were 4.94-4.22 and the titrable acidity was 0.63-0.98.